The Period of Progress of Islamic Civilization - Basri, Muhammad; Al-Hadid, Nurul Hadidah; Tanjung, Ziha Fida Utami; Hasanah, Nur (EDUCTUM: Journal Research, 2024)
The Islamic civilization's period of advancement from 600-1000 CE, often referred to as the Golden Age of Islam, represents a pivotal era in human history marked by unity in Islamic values, a strong moral foundation, and a cohesive identity among Muslims. This epoch reached its zenith during the times of the Rightly Guided Caliphs, the Umayyad Dynasty, and the Abbasid Dynasty. Key factors, such as steadfast adherence to Islamic values, laid the groundwork for a robust moral foundation and a detailed Islamic legal system. Cultural heritage emerged as a primary driver for scientific development, with translation centers and universities fostering a dynamic intellectual environment. The Umayyad period witnessed territorial expansion into North Africa, the Middle East, and Spain, leaving a significant impact on cultural and social progress. Despite internal challenges, the Umayyad's success provided a basis for advancements in science, art, and architecture. The Abbasid Golden Age saw the establishment of the House of Wisdom, a translation center that amalgamated classical knowledge. The Abbasids became intellectual and cultural hubs, making strides in science, medicine, art, and architecture. Influential figures such as Ibn Rushd, Al-Ghazali, Al-Kindi, Al-Farabi, and Ibn Sina made monumental contributions across various fields of study. In conclusion, the Islamic Golden Age demonstrated that the harmony between Islamic values, scientific development, and cultural appreciation served as the primary driving force, while future research prospects may explore practical applications in contemporary contexts, supporting positive developments in various aspects of human life.